Pelvic organ prolapse in rural Nepalese women of reproductive age groups: What makes it so common? - Gurung, Geeta; Rana, Ashma; Amatya, Archana; Bista, Keshang D; Joshi, Ananda B; Sayami, Jamuna (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Aim: To find out the prevalence, aetiopathogenesis and the magnitude of problems of pelvic organ prolapse (POP) among married women of reproductive age (MWEA) in the rural Nepalese community. Methods: A cross-sectional descriptive study conducted in eight selected districts (mountain/ hills to terai region) of Nepal linking community to health services. Proportionate samples of MWRA (15-49 years) in total samples of 2849 were interviewed using questionnaires and clinical examinations were made in health facililities. Results: Among 2849 women who agreed to take part on the study when interviewed (by enumerators with pretested questioners) 2070 (72.6%) came for assessment. POP was diagnosed in 207/2070 giving the incidence as 10% being commoner in the planes (8:1) than mountains. POP formed 2.8% of adolescent due to early marriage d" 15 years in (50%) and unsupported delivery by skilled birth attendant (SBA) out of health facilities (99.2%). Resumption of manual labor after delivery less than a month was (83.8%) and parity was responsible to some extent as P(1-3) occupied by T!. Mean duration of suffering being 7.8 years (e" 10 years in ¼.) having II°/III° or procidentia rectovaginal/ vesicovaginal fistula, urinary incontinence (stress/urge), bleeding, discharge from sore and ulceration, coital problem, urination/ defecation problem walking, sitting, back ache and chronic abdominal pain S!. Conclusion: In this large reproductive morbidity study including women in the rural community of varied ethenic groups from diverse ecology, basic community survey linked to clinical assessment in the health facility found the incidence of POP to be much higher in planes than hills giving unusually lower prevalence rate for POP as 10% than other clinic based studies. doi:10.3126/njog.v2i2.1453 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 35 - 41